Planning, Accounting and Control as Risk Management Tools for Small Business Investment Projects - Svitlana Bondarenko; Natalya Shlafman; Nataliia Kuprina; Olga Kalaman; Olena Moravska; Natalia Tsurkan (Ital Publication, 2021)
The purpose of this study is to develop scientifically sound proposals and recommendations for the implementation of planning, accounting and control tools in risk management of investment projects of small businesses. The relevance of this study is due to the need to provide small businesses with effective methods of risk management of the investment project, which can significantly reduce the negative impact of risk factors and achieve a significant effect from the investment. To achieve the goal of the study, methodological approaches were used to assess the risk sustainability of the enterprise, based on the assessment of the resource potential of the enterprise. A system of indicators is proposed to assess the quality of enterprise resources. Theoretical and methodological approaches to the formation of an early warning system in risk management have been developed. The proposed concept of indicative management includes tools for indicative control of investment projects in relation to the risk sustainability of the enterprise from the standpoint of its resource provision. Risks in this case become key indicators to which management actions should be directed. The introduction of a risk passport is proposed as a tool for early warning of crisis phenomena in small enterprises. The authors proved that the risk prevention system should be integrated into the overall organizational structure and become part of the enterprise management system. Indicative management is proposed as a tool for implementing functional strategies to prevent or eliminate threats and maximize their strengths and capabilities. Doi: 10.28991/esj-2021-01302 Full Text: PDF